The effectiveness of social cognitive career theory on career decision making - Kusumawati, Eny; Wahyuningsih, Diana Dewi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2020)
Students with high academic anxiety can cause a decrease in motivation to learn. This kind of situation will harm the learning achievement achieved by students. The purpose of this study was to examine the influence of social cognitive career theory on improving student career decision making. This study used a randomized experimental pretest-posttest control group design. A total of 16 students of VHS Boyolali were the subjects in this study. Selection of subjects using purposive sampling technique which is based on the criteria of low career decision-making ability, obtained from the score of career decision making scale. The data analysis technique used was the Wilcoxon test. The results of statistical tests show that there is an effect of social cognitive career theory on increasing student career decision making. The findings of this study prove that the social cognitive career theory is effective in improving student career decision making at VHS Boyolali.